Public education and R&D-based economic growth - Katharina Werner; Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We analyze the short- and long-run effects of public education on economic growth and welfare. In so doing, we extend an R&D-based economic growth model by including a governmental sector that levies labor income taxes and uses the proceeds to finance teachers. An increase in the tax rate reduces consumption possibilities (and thereby individual utility), and the number of workers available for final goods production and research. At the same time, however, it increases the educational resources available per pupil. Consequently, economic growth slows down immediately after an increase in educational investments but it speeds up during the transition toward the long-run balanced growth path. Altogether, this implies a dynamic tradeoff in the sense that current cohorts loose due to educational reform, whereas future cohorts gain. We show that there exists an interior welfare-maximizing level of the provision of public education for each time horizon and show that it is higher than the levels we typically observe in industrialized countries. Since the transitional effects of an education reform on growth and welfare can be negative, our framework has the potential to explain resistance against long-run welfare improving education reforms.
Keywords: I25; J24; O31; 330